Analisis Penyebab Kesalahan yang Biasa Terjadi dalam Menyelesaikan Soal Cerita Bilangan Bulat - Intan Dwi Maharani; Diana Ermawati; Lovika Ardana Riswari (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2024)
The main objective of this research is to identify the causes of errors in solving mathematical problems in class VI students at SD N Bulungcangkring. This research uses a qualitative descriptive research type. Subjects were selected using a purposive technique. So, from 31 students at SD N 1 Bulungcangkring, the researchers chose 6 students who had 2 low, 2 medium and 2 high mathematical abilities with the consideration of selecting students with different mathematical abilities. The research results show that students errors in solving whole number story problems are influenced by several factors such as not understanding basic concepts, errors in algorithms or procedures and a lack of understanding of the steps in mathematical solving. From these results it can be concluded that students' errors in solving integer story problems are influenced by several factors such as not understanding basic concepts, errors in algorithms or procedures, and lack of understanding of the mathematical calculation steps needed to solve the problem. All of this suggests the need for a more in-depth learning approach to concepts, practice in applying relevant formulas and steps, and an emphasis on a thorough understanding of how to solve mathematical problems.